2004
DOI: 10.1002/crat.200310150
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity in Tl4S3 layered single crystals

Abstract: Photoconductivity measurements are carried out in this work for single crystals of Tl 4 S 3 compound by using both pulsed excitation (a.c) and steady state (a.c) methods in order to elucidate the nature of photoconductivity (PC) in this compound. Results are reported in the temperature range from 77 to 300K, excitation intensity range from 1800 to 3300Lux, applied voltage range from 8 to 14V, and wavelength range from 840 to 1450nm. Both of the ac-photoconductivity (ac-PC) and the spectral distribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 19 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…The optical absorption studies of Tl 2 S have been investigated by Estrella et al [9] and suggest that there are direct forbidden transitions with a band gap of 1.12 eV. Characteristics of photoconductivity in Tl 2 S layered single crystals have been reported in our paper [10], and the same studies for Tl 4 S 3 have been reported in our paper [11].…”
Section: Am Badrsupporting
confidence: 80%
“…The optical absorption studies of Tl 2 S have been investigated by Estrella et al [9] and suggest that there are direct forbidden transitions with a band gap of 1.12 eV. Characteristics of photoconductivity in Tl 2 S layered single crystals have been reported in our paper [10], and the same studies for Tl 4 S 3 have been reported in our paper [11].…”
Section: Am Badrsupporting
confidence: 80%
“…As intense light falls on the sample, the lifetime decreases [24]. In Stockmann model, a two level scheme is proposed to explain negative photoconductivity [25].…”
Section: Characterizationmentioning
confidence: 99%
“…As intense light falls on the sample, the lifetime decreases [21]. In Stockmann model, a two level scheme is proposed to explain negative photoconductivity [22].…”
Section: Characterizationmentioning
confidence: 99%